Benevolent Sexism and Obedience in Adolescent Girls - Nurfitriany Fakhri; Sahril Buchori; Irdianti Irdianti (Jurnal Scientia, 2023)
Sexism is manifested through the division of gender-based roles and the unequal distribution of rights and opportunities. One of one sexism is benevolent sexism . The objective of this study is to investigate the correlation between benevolent sexism and obedience with women. The population of this study was adolescent girls, with a sample number of 75 subjects. This research uses a correlative method through data collection done by using a scale benevolent sexism and the scale of obedience. The data that has been gathered is subsequently subjected to regression statistical analysis. The findings indicate a statistically significant correlation between benevolent sexism and obedience with norms among adolescent females.